Detecting geriatric needs in older patients with breast cancer through use of a brief geriatric screening tool. Issue 6 (November 2019) - Kikuchi, Robin; Broadwater, Gloria; Shelby, Rebecca; Robertson, Jessica; Zullig, Leah L.; Maloney, Bailey; Meyer, Claudia; Mungal, Daniel; Marcom, Paul K.; Kanesvaran, Ravindran; White, Heidi; Kimmick, Gretchen
Abstract: Introduction: Identification of geriatric syndromes is important for determining functional age and optimizing care for people with cancer. Based on administration of a geriatric screening tool, we aimed to describe needed resources for geriatric syndromes, including lack of social support, depressed mood, deficits in instrumental and activities of daily living (IADL/ADL), falls, nutritional issues, polypharmacy, ability to pay for medications, and memory deficits, in a population of patients with breast cancer. Methods: Consecutive medical oncology patients with breast cancer age 65 years and older, seen at a tertiary care center, completed a screening tool, adapted from Overcash 2006, consisting of a nurse-administered memory assessment and a one-page, self-administered questionnaire. Responses identified geriatric syndromes. Demographics and clinical information were retrospectively gathered. Frequencies and means were used to describe data. Results: From January 2012 through July 2014, patients (n = 429) completed the screening tool as part of routine care. Study group had mean age 76 years (range 65–89), mean time since diagnosis 6.5 years, 91% non-metastatic disease, mean Charlson Comorbidity score 1.8 (range 0–10). Treatment included partial mastectomy (49%), adjuvant radiation (43%), chemotherapy (25%), and endocrine therapy (61%). The screening tool identified need for social support (8%); depression (31%); mobility issues (20%); falls (28%); nutritional needs (33%); polypharmacy (83%); and memory deficit (19%). Conclusion: This screening tool identified geriatric syndromes requiring attention in many patients with breast cancer presenting for medical oncology appointments. In oncology practice, need for referral networks to address geriatric syndromes should be assessed.